Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If m=cosA-sinA and n=cosA+sinA. Show that m*m-n*n= -4sinA*cosA/cos*cosA-sinA*sinA=-4cotA-tanA

If m=cosA-sinA and n=cosA+sinA. Show that m*m-n*n= -4sinA*cosA/cos*cosA-sinA*sinA=-4cotA-tanA

Grade:10

1 Answers

Arun
25763 Points
3 years ago
Dear student
I will write cos A as c and sin A as s for simplicity.
m/n - n/m
= (m² - n²)/mn
= (c² + s² - 2c*s - c² -s² - 2c*s )/ (c-s)(c+s)
= - 4 c *s / c² - s²
Regards
Arun (askIITians forum expert)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free